Epidemiology, pathology, prevention, and control strategies of inclusion body hepatitis and hepatitis-hydropericardium syndrome in poultry: A comprehensive review - El-Shall, Nahed A.; El-Hamid, Hatem S. Abd; Elkady, Magdy F.; Ellakany, Hany F.; Elbestawy, Ahmed R.; Gado, Ahmed R.; Geneedy, Amr M.; Hasan, Mohamed E.; Jaremko, Mariusz; Selim, Samy; El-Tarabily, Khaled A.; El-Hack, Mohamed E. Abd (Frontiers in Veterinary Science, 2022)
Infection with fowl adenoviruses (FAdVs) can result in a number of syndromes in the production of chicken, including inclusion body hepatitis (IBH), hepatitis-hydropericardium syndrome (HHS), and others, causing enormous economic losses around the globe. FAdVs are divided into 12 serotypes and five species (A–E; 1–8a and 8b−11). Most avian species are prone to infection due to the widespread distribution of FAdV strains. The genus aviadenovirus, which is a member of the adenoviridae family, is responsible for both IBH and HHS. The most popular types of transmission are mechanical, vertical, and horizontal. Hepatitis with basophilic intranuclear inclusion bodies distinguishes IBH, but the buildup of translucent or straw-colored fluid in the pericardial sac distinguishes HHS. IBH and HHS require a confirmatory diagnosis because their clinical symptoms and postmortem abnormalities are not unique to those conditions. Under a microscope, the presence of particular lesions and inclusion bodies may provide clues. Traditional virus isolation in avian tissue culture is more delicate than in avian embryonated eggs. Additionally, aviadenovirus may now be quickly and precisely detected using molecular diagnostic tools. Preventive techniques should rely on efficient biosecurity controls and immunize breeders prior to production in order to protect progeny. This current review gives a general overview of the current local and global scenario of IBH, and HHS brought on by FAdVs and covers both their issues and preventative vaccination methods.